Golimumab administered subcutaneously every 4 weeks in ankylosing spondylitis: 5-year results of the GO-RAISE study. Issue 4 (11th November 2014) - Deodhar, Atul; Braun, Jürgen; Inman, Robert D; van der Heijde, Désirée; Zhou, Yiying; Xu, Stephen; Han, Chenglong; Hsu, Benjamin
Abstract : Objective: Assess golimumab efficacy/safety through 5 years in patients with active ankylosing spondylitis (AS). Methods: 356 patients with AS were randomly assigned to placebo, golimumab 50 mg or 100 mg every 4 weeks. At week 16, patients with inadequate response early escaped with blinded dose adjustments (placebo to 50 mg, 50 mg to 100 mg). At week 24, all patients receiving placebo crossed over to 50 mg. Blinded active therapy continued through week 104; from week 104 to week 252, the golimumab dose could be adjusted. Intent-to-treat and observed efficacy data were assessed by randomised treatment groups. Results: At week 256, and with >4.5 years of golimumab, overall intent-to-treat Assessment in SpondyloArthritis international Society criteria for 20% improvement (ASAS20) and ASAS40 response rates were 66.0% (235/356) and 57.0% (203/356), respectively; Bath AS Disease Activity Index 50% improvement response was 55.9% (199/356). Observed response rates among the 255 (72%) patients who continued golimumab through week 252 were consistent, albeit somewhat higher. Among patients who increased golimumab from 50 to 100 mg, 60.6% (20/33) and 44.7% (17/38) achieved ASAS20/ASAS40 responses, respectively, following ≥2 consecutive doses of golimumab 100 mg. Golimumab safety through week 268 was similar to that through week 24 regardless of dose. Conclusions: Clinical improvements observed in patients treated with golimumab through week 24 were sustained through week 256 (5 years). Long-term golimumab safety is consistent with that of other established tumour-necrosis-factor-antagonists. Trial registration number: ClinicalTrials.gov: NCT00265083 .